2012
DOI: 10.1002/agr.21312
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Performance of Farmer Companies in Sri Lanka: Lessons for Farmer‐Owned Marketing Firms

Abstract: Sri Lanka introduced farmer companies to link smallholders with high-value markets. This study examines how the institutional, group, and management characteristics of these farmer companies affect their performance. Theories about causal relationships are tested using a combination of qualitative and quantitative methods. The results indicate that farmer companies perform better when shares are tradable between members, and patrons pay and receive market-related prices for their inputs and products. All direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…For example, participants stated that 'Taiwanese farmers have abundant opportunities, but numerous innovative actions are restricted by government regulations' (M2), and that 'The government should determine Taiwan's position and strategic values in the global market, and then make policies to guide domestic farmers' (M4). This result agreed with prior research (Hartwich & Negro, 2010;Rosairo et al, 2012), which suggests that the government should have a clear plan to support innovation through various funding schemes, and simultaneously foster agribusiness collaboration.…”
Section: Agricultural Development Trendssupporting
confidence: 81%
See 1 more Smart Citation
“…For example, participants stated that 'Taiwanese farmers have abundant opportunities, but numerous innovative actions are restricted by government regulations' (M2), and that 'The government should determine Taiwan's position and strategic values in the global market, and then make policies to guide domestic farmers' (M4). This result agreed with prior research (Hartwich & Negro, 2010;Rosairo et al, 2012), which suggests that the government should have a clear plan to support innovation through various funding schemes, and simultaneously foster agribusiness collaboration.…”
Section: Agricultural Development Trendssupporting
confidence: 81%
“…Hartwich and Negro (2010) showed that governments support innovation initiatives through various funding schemes that do not explicitly foster collaboration. Rosairo, Lyne, Martin, and Moore (2012) further indicated that agribusiness management problems may increase if governments do not plan to facilitate their policies.…”
Section: External Environmentmentioning
confidence: 99%
“…Punj and Stewart (1983) reported that hierarchical cluster analysis can be used as a classification tool in survey research. Knight, Lyne, and Roth (2003) and Rosairo et. al.…”
Section: Collection Of Data and Analysismentioning
confidence: 92%
“…Farmer-owned companies can be considered as an ideal rural socio-economic unit if suitable institutional arrangements are in place for the sustainability of the company (Rosairo et al, 2012). Export production villages that bring producers of a certain value added product into one company, is a rural development concept introduced in Sri Lanka (Kulatunga, 1993) but without much success (Rosairo, 2010).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…OMA encompasses metrics relating to observable membership characteristics (Bhuyan, 2007;Chagwiza et al, 2016;Rosairo et al, 2012), particularly with respect to user-benefit and user-control arrangements. More specifically, this sub-category relates to pricing, delivery, services, and governance data, like prices paid to members by the co-op, the percentage of inselling (or side-selling), the scope and quality of services members receive, and the governance systems and procedures (e.g., CEO tenure, secret ballots, audited accounts, available information to members).…”
Section: Objective Membership Appraisal (Oma)mentioning
confidence: 99%